(untitled) (Philosophy and Progress, 2023)
Religious freedom is considered a fundamental human right and the cornerstone of human dignity. Islam, being a universal religion, protects the rights of every individual, and thus, preserves and upholds the dignity of human persons irrespective of their religious convictions. This study aims to understand Islamic perception of religious freedom from a historical point of view. It is based on textual analysis and historical interpretation of the Qur’an and Sunnah. It also supports its case by analysing some Muslim ruler’s treatment of other religions. The study shows that Islam provides complete freedom to every individual so long as it does not violate or interfere the right of others, and explicitly prohibits all kinds of intervention in matters of religious beliefs and practices. Though the Prophetic tradition “whoever changes his religion, kill him” seems contradictory to freedom of religion, this has been contextualised in particular situation by contemporary Islamic scholars. The study concludes that the Qur’anic teachings, the Prophetic practices and Muslim rulers’ treatment of other religions affirm that Islam provides equal opportunities to all regardless of their attachments to any religion or ideology, and Muslims can neither force any body to accept Islam nor impose anything against his/her will. Philosophy and Progress, Vol#71-72; No#1-2; Jan-Dec 2022 P 1-27